The Challenges of Teaching Indonesian History in The Teaching Factory Learning Model in Vocational High School - Riski Gustiar; Kurniawati Kurniawati; Murni Winarsih (STAI Hubbulwathan Duri, 2021)
This study aims to identify teachers' challenges in teaching Indonesian History at SMK using the Teaching Factory learning model. This study uses qualitative methods by taking research at SMKN 28 South Jakarta. The analysis used is the grounded theory approach of Strauss and Corbin. The results illustrate three interrelated things: the Teaching Factory concept, the implementation and challenges faced by Indonesian History subject teachers, and the teacher's efforts to face these challenges. Based on the research results, it shows that the challenge faced by the teacher is the compaction of Indonesian History material in SMK. The teacher must accommodate students who cannot participate in learning activities in class and the absence of teaching materials based on the Teaching Factory. Efforts to answer these challenges based on the research results in the field can be overcome by; adjusting Indonesian History material in vocational schools, providing teaching materials that are easy to understand for students to learn independently, and making learning innovations in the skills process (KI-4).